Loss of bioactive microRNAs in cow's milk by ultra‐high‐temperature treatment but not by pasteurization treatment. (2nd November 2021) - Zhang, Yangdong; Xu, Qingbiao; Hou, Jinxiu; Huang, Guoxin; Zhao, Shengguo; Zheng, Nan; Wang, Jiaqi
Abstract: BACKGROUND: Milk microRNA (miRNA) with bioactivity is beneficial for human health. However, the effect of heat treatment on miRNA in milk is still not clear. In this study, the miRNAs in raw (RM), pasteurized (PM) and ultra‐high‐temperature (UHT) milk (UM) from the same batch were extracted, sequenced and analyzed. RESULTS: The results showed that there was a significant difference in miRNAs between RM and UM, but not between RM and PM. The total read counts of milk miRNAs were significantly decreased by heat treatment, with the least counts in UM ( P  < 0.05). The average length and GC percentage of miRNAs were significantly reduced by heat treatment ( P  < 0.05), while there was no significant difference in these terms between RM and PM. The content of miRNAs was verified by qPCR, finding that miR‐17‐5p, miR‐25, miR‐27b and miR‐9‐5p were significantly reduced in UM ( P  < 0.05) but not significantly affected in PM (except miR‐27b). In addition, the targeting gene ontology enrichment functions of the different presented miRNAs were mostly enriched in biological process, cellular component and molecular function. The top 20 enriched miRNAs with different levels in heat‐treated milk were identified by the Kyoto Encyclopedia of Genes and Genomes enrichment analysis. Interestingly, most of the functions of these miRNA targeting genes are involved in cancer or inflammation activity. CONCLUSION: This study revealed that the bioactive miRNA in RM was lost after UHT treatment but not in pasteurized treatment. © 2021 Society of Chemical Industry.